Reprogramming the Biosynthesis of Cyclodepsipeptide Synthetases to Obtain New Enniatins and Beauvericins. (5th January 2016) - Zobel, Sophia; Boecker, Simon; Kulke, Daniel; Heimbach, Dirk; Meyer, Vera; Süssmuth, Roderich D.
Abstract: Non‐ribosomal peptide synthetases are complex multimodular biosynthetic machines that assemble various important and medically relevant peptide antibiotics. An interesting subgroup comprises the cyclodepsipeptide synthetases from fungi synthesizing cyclohexa‐ and cyclo‐octadepsipeptides with antibacterial, anthelmintic, insecticidal, and anticancer properties; some are marketed drugs. We exploit the modularity of these highly homologous synthetases by fusing the hydroxy‐acid‐activating module of PF1022 synthetase with the amino‐acid‐activating modules of enniatin and beauvericin synthetase, thus yielding novel hybrid synthetases. The artificial synthetases expressed in Escherichia coli and the fungus Aspergillus niger yielded new cyclodepsipeptides, thus paving the way for the exploration of these derivatives for their bioactivity. Abstract : Module swapping of NRPSs : Fusing the first module of the synthetase PSYN with the second module of ESYN or BSYN yields active chimeric synthetases that catalyze the formation of new cyclodepsipeptide derivatives. The experiments provide access to compounds not found in nature.